2018
DOI: 10.1038/aps.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

Heart-type fatty acid binding protein (H-FABP) as a biomarker for acute myocardial injury and long-term post-ischemic prognosis

Abstract: Acute myocardial infarction (AMI) is a life-threatening event. Even with timely treatment, acute ischemic myocardial injury and ensuing ischemia reperfusion injury (IRI) can still be difficult issues to tackle. Apart from radiological and other auxiliary examinations, laboratory tests of applicable cardiac biomarkers are also necessary for early diagnosis and close monitoring of this disorder. Heart-type fatty acid binding protein (H-FABP), which mainly exists inside cardiomyocytes, has recently emerged as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 74 publications
1
68
0
3
Order By: Relevance
“…242 Since H-FABP exists mainly in cardiomyocytes, it becomes a potentially promising biomarker for myocardial injury. 36,244 FABP family members involved in active fatty acid metabolism, functionally H-FABP also do the same, where it transports FAs from the cell membrane to mitochondria for oxidation. 245 This FABP are believed to participate in the uptake, intracellular metabolism, and transport of long-chain polyunsaturated fatty acids.…”
Section: Cardiac Myosin Light Chain Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…242 Since H-FABP exists mainly in cardiomyocytes, it becomes a potentially promising biomarker for myocardial injury. 36,244 FABP family members involved in active fatty acid metabolism, functionally H-FABP also do the same, where it transports FAs from the cell membrane to mitochondria for oxidation. 245 This FABP are believed to participate in the uptake, intracellular metabolism, and transport of long-chain polyunsaturated fatty acids.…”
Section: Cardiac Myosin Light Chain Kinasementioning
confidence: 99%
“…It is noteworthy that circulating H-FABP concentrations are elevated in NAFLD and metabolic syndrome as well as in obesity, [257][258][259][260][261] signifying that H-FABP is one of the markers of insulin resistance and subclinical myocardial damage that exist in these patients. For this reason, the diagnostic accuracy of H-FABP may make it a useful indicator for the early prediction of high-risk patients in the general population, 244,262 as well as being considered a useful marker for assessing ongoing myocardial damage.…”
Section: Cardiac Myosin Light Chain Kinasementioning
confidence: 99%
“…This so-called "wounding" of myocytes was observed, even after short-term ventricular stress, and it may play an important role in diverse auto-and paracrine mechanisms in the pathogenesis of HF [20]. The elimination of H-FABP takes place via the kidney, explaining a shorter diagnostic window in patients with normal renal function [22]. Kleine et al, for example, reported that H-FABP plasma levels returned to baseline within 20 hours after the onset of symptoms in patients with acute myocardial infarction [23].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Restoration of coronary blood flow is the most effective intervention to minimize myocardial ischemic injury, leading to improvement in survival. 3,4 However, paradoxically, the process of myocardial reperfusion itself can induce additional cardiac damage and pathological remodeling, referred to as "myocardial ischemia/reperfusion (I/R) injury". 3,5 Although the underlying mechanisms of this have not been clearly defined, accumulating evidence indicates that activation of cardiac apoptosis plays an important role in the pathophysiology of reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%